Early pulmonary events of nose‐only water pipe (shisha) smoking exposure in mice. Issue 3 (16th March 2015) - Nemmar, Abderrahim; Hemeiri, Ahmed Al; Hammadi, Naser Al; Yuvaraju, Priya; Beegam, Sumaya; Yasin, Javed; Elwasila, Mohamed; Ali, Badreldin H.; Adeghate, Ernest
Abstract: Water pipe smoking (WPS) is increasing in popularity and prevalence worldwide. Convincing data suggest that the toxicants in WPS are similar to that of cigarette smoke. However, the underlying pathophysiologic mechanisms related to the early pulmonary events of WPS exposure are not understood. Here, we evaluated the early pulmonary events of nose‐only exposure to mainstream WPS generated by commercially available honey flavored " moasel " tobacco. BALB/c mice were exposed to WPS 30 min/day for 5 days. Control mice were exposed using the same protocol to atmospheric air only. We measured airway resistance using forced oscillation technique, and pulmonary inflammation was evaluated histopathologically and by biochemical analysis of bronchoalveolar lavage (BAL) fluid and lung tissue. Lung oxidative stress was evaluated biochemically by measuring the level of reactive oxygen species (ROS), lipid peroxidation (LPO), reduced glutathione (GSH), catalase, and superoxide dismutase (SOD). Mice exposed to WPS showed a significant increase in the number of neutrophils ( P  < 0.05) and lymphocytes ( P  < 0.001). Moreover, total protein ( P  < 0.05), lactate dehydrogenase ( P  < 0.005), and endothelin ( P  < 0.05) levels were augmented in bronchoalveolar lavage fluid. Tumor necrosis factor α ( P  < 0.005) and interleukin 6 ( P  < 0.05) concentrations were significantly increased in lung following the exposure to WPS. Both ROS ( P  < 0.05) and LPO ( P  < 0.005) in lung tissue were significantly increased, whereas the level and activity of antioxidants including GSH ( P  < 0.0001), catalase ( P  < 0.005), and SOD ( P  < 0.0001) were significantly decreased after WPS exposure, indicating the occurrence of oxidative stress. In contrast, airway resistance was not increased in WPS exposure. We conclude that subacute, nose‐only exposure to WPS causes lung inflammation and oxidative stress without affecting pulmonary function suggesting that inflammation and oxidative stress are early markers of WPS exposure that precede airway dysfunction. Our data provide information on the initial steps involved in the respiratory effects of WPS, which constitute the underlying causal chain of reactions leading to the long‐term effects of WPS. Abstract : Our data demonstrate that subacute (5‐day) nose‐only exposure to WPS caused pulmonary inflammation and oxidative stress without affecting pulmonary function suggesting that inflammation and oxidative stress are early markers of WPS exposure that precedes airway dysfunction. Our data provide specific information on the initial changes in the lung after subacute exposure to WPS, which may constitute the underlying causal chain of reactions leading to the ultimate long‐term pulmonary effects. Our study provides biological plausibility for the injurious effects of WPS after a relatively short duration of exposure, and support interventions to control the worldwide spread of WPS, particularly among the young generation.